Autosomal Recessive Cerebellar Ataxias With Elevated Alpha‐Fetoprotein: Uncommon Diseases, Common Biomarker. Issue 12 (12th October 2020) - Renaud, Mathilde; Tranchant, Christine; Koenig, Michel; Anheim, Mathieu
ABSTRACT: alpha‐Fetoprotein (AFP) is a biomarker of several autosomal recessive cerebellar ataxias (ARCAs), especially ataxia telangiectasia (AT) and ataxia with oculomotor apraxia (AOA) type 2 (AOA2). More recently, slightly elevated AFP has been reported in AOA1 and AOA4. Interestingly, AOA1, AOA2, AOA4, and AT are overlapping ARCAs characterized by oculomotor apraxia, with oculocephalic dissociation, choreo‐dystonia, and/or axonal sensorimotor neuropathy, in addition to cerebellar ataxia with cerebellar atrophy. The genetic backgrounds in these disorders play central roles in nuclear maintenance through DNA repair [ ATM (AT), APTX (AOA1), or PNKP (AOA4)] or RNA termination [ SETX (AOA2)]. Partially discriminating thresholds of AFP have been proposed as a way to distinguish between ARCAs with elevated AFP. In these entities, elevated AFP may be an epiphenomenon as a result of liver transcriptional dysregulation. AFP is a simple and reliable biomarker for the diagnosis of ARCA in performance and interpretation of next‐generation sequencing. Here, we evaluated clinical, laboratory, imaging, and molecular data of the group of ARCAs that share elevated AFP serum levels that have been described in the past two decades. © 2020 International Parkinson and Movement Disorder Society